2022
DOI: 10.1186/s12913-022-07628-9
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis attendance patterns and health care utilisation of Aboriginal patients attending dialysis services in urban, rural and remote locations

Abstract: Background Aboriginal people in the Northern Territory (NT) suffer the heaviest burden of kidney failure in Australia with most living in remote areas at time of dialysis commencement. As there are few dialysis services in remote areas, many Aboriginal people are required to relocate often permanently, to access treatment. Missing dialysis treatments is not uncommon amongst Aboriginal patients but the relationship between location of dialysis service and dialysis attendance (and subsequent hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The present study found that haemodialysis patients tend to shorten treatment times by about 20 min on average, supporting previous studies that found patients shorten treatment times by more than 10 min (Al Salmi et al, 2018; Gorham et al, 2022; Saran et al, 2003; Sousa et al, 2019). This finding is concerning, because according to many studies in the field, adherence to haemodialysis is critical to overall treatment effectiveness, and failure to adhere to treatment can lead to poor therapeutic outcomes and increased financial costs (Kammerer et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…The present study found that haemodialysis patients tend to shorten treatment times by about 20 min on average, supporting previous studies that found patients shorten treatment times by more than 10 min (Al Salmi et al, 2018; Gorham et al, 2022; Saran et al, 2003; Sousa et al, 2019). This finding is concerning, because according to many studies in the field, adherence to haemodialysis is critical to overall treatment effectiveness, and failure to adhere to treatment can lead to poor therapeutic outcomes and increased financial costs (Kammerer et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Una limitación de este estudio, debido a las variables disponibles para el análisis, es la imposibilidad de modelizar la función de riesgo para comprobar el efecto de la comorbilidad de los pacientes, así como estudiar la calidad de vida y realizar un análisis de coste-eficiencia. Los datos bibliográficos existentes muestran que la US en áreas urbanas son más coste-eficientes que las situadas de áreas rurales muy alejadas del centro terciario 37 , pero cuando se ajusta por variables como la edad, la comorbilidad o tiempo de permanencia en HD, las unidades eficientes son la US rurales 38 . Una alternativa a las US rurales sería la HD domiciliaria.…”
Section: Discussionunclassified
“…2 Townsville Renal Service, Townsville University Hospital, 100 Angus Smith Drive, Douglas, QLD 4814, Australia. 3 College of Science and Engineering, James Cook University, Nguma-Bada Campus, PO Box 6811, Cairns, QLD 4870, Australia. 4 Centre for Quality and Patient Safety Research, Institute for Health Transformation, Deakin University, Melbourne Burwood Campus, 221 Burwood Highway, Burwood, VIC 3125, Australia.…”
Section: Fig 8 Participant Flow Diagrammentioning
confidence: 99%
“…Consequently, many patients have had to relocate from their rural or remote communities to more densely populated cities to access dialysis treatment. Geographical access to haemodialysis has been shown to affect attendance at scheduled dialysis sessions, [2] particularly for First Nations Australians [3]. First Nations Australians comprise 9.04% of the total population within the Townsville Hospital and Health Service.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation